(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Abstract: this article provides an overview of the classification of compound words in both traditional and modern linguistic approaches. Key terms discussed include endocentric, exocentric, coordinative, subordinative, and appositional compounds. The article examines how the analysis and categorization of compound words has evolved over time, highlighting the contributions of prominent linguists and the ongoing debates within the field.